DALI Compatible Smart LED Driver Controller with Wi-Fi Communication - EKREN, NAZMİ (My University, 2023)
DALI (Digital Addressable Lighting Interface) is one of the communication types commonly used in smart LED systems. It is a type of wired communication and is usually used in large facilities. The fact that it provides energy efficiency and supports user comfort increases the preferability of these systems. Energy savings can be achieved by making scenario definitions for LED drivers. An example is ensuring that the LED driver works at a certain time interval by setting the timing gap. Thanks to the dimming feature, it can be ensured that the light intensity remains at a certain level. With the help of sensors, the brightness level of the LED driver can be adjusted according to the light level outside. In this study, the design of the LED driver controller, which is controlled via Wi-Fi communication with the user interface supporting the DALI protocol, will be mentioned. Communication of the developed controller with the user interface will be carried out wirelessly. Wi-Fi has been preferred. The hardware part of this developed system consists of a processor-supported control circuit, a communication unit circuit and DALI hardware circuit parts. The designed smart LED driver controller is capable of fulfilling the standard requirements of the DALI protocol. It converts the command information received over Wi-Fi to the DALI protocol and provides control of the LED driver. The control device will be controlled and monitored via smartphone, computer, tablet, and web. In conclusion, with the commands given from the user interface, the LED driver turns on/off the light, increases / decreases the light intensity and similar commands available in DALI standards are controlled.
Keywords: Elektrik-Elektronik Mühendisliği; Elektronik; Mühendislik ve Teknoloji; Electrical and Electronics Engineering; Electronic; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; Elektrik ve Elektronik Mühendisliği; Sinyal İşleme; Fizik Bilimleri; Electrical and Electronic Engineering; Signal Processing; Physical Sciences